Estudo da penetração de agentes ácidos para o condicionamento do esmalte dental em cimentos à base de hidróxido de cálcio. - dos Santos Cruz, C. A.; Adabo, Gelson Luis [UNESP]; Rettondini, W. C.; de Sa, D. N.; da Silva Filho, F. P. (My University, 1990)
It was verified the penetration of phosphoric acid into 3 commercial calcium hydroxide-based cements (Life, Renew and Prisma VLC Dycal). The colorimetric method employed permitted the identidication of phosphorus amount in representative samples of 6 successive layers 0.1 mm thick of each material. The acid etching used were the commercial products Scotchbond Etching Gel--3M at 36.114% by weight and Solução Condicionadora--Johnson & Johnson at 36.054% by weight. The contact time was 60 seconds. The result showed that layers 0.1 mm tick for Life and Prisma VLC Dycal and 0.2 mm thick for Renew were able to block the penetration of phosphoric acid solution whereas layers 0.1 mm thick for the 3 cements were able to block the penetration of phosphoric acid gel.
Penetration of calcium hydroxide based cements by dental enamel conditioning acids
Keywords: calcium hydroxide; phosphoric acid; phosphorus; tooth cement; cementation; colorimetry; drug effect; enamel; endodontics; Acid Etching, Dental; Calcium Hydroxide; Colorimetry; Dental Cements; Dental Enamel; Dental Enamel Solubility; Dental Pulp Capping; English Abstract; Phosphoric Acids; Phosphorus